Cognitive Assessment Techniques on Student Learning Outcomes in SKI Subjects at MA Darul Ukhuwwah Putri 2 Singosari Malang - Masruri, M. Sauqi Iza; Kumala Sari, Meilia; Azwary, Khoula (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Evaluation has a very significant role in the educational context, and effective and efficient evaluation is carried out continuously and comprehensively. Through the evaluation process, teachers can obtain an overview of the progress and achievements that have been achieved by students. One aspect of assessment in education, especially in Islamic cultural history subjects, is the cognitive domain. So, the purpose of conducting this research is to find out how the assessment techniques used by teachers affect student learning outcomes in SKI subjects at MA Darul Ukhuwwah Putri 2 Singosari Malang. The research method used in this research is descriptive qualitative research. The results of this research state that cognitive domain assessment is an activity carried out by teachers to measure students' understanding of learning. The cognitive domain assessment techniques used in SKI subjects at MA Darul Ukhuwwah are divided into 3 types, namely: written tests (multiple choice, short description and essay), group discussions, and oral tests. The written test can be carried out by giving several written questions to students via LKS/or a package book printed by MA Darul Ukhuwah Putri 2 Singosari Malang which contains questions and statements related to the material they have studied. The teacher carries out an oral test at the end of the lesson by conducting questions and answers between students and the teacher regarding the material they have studied, which is usually done during final exams.